Communicative Language Teaching (CLT) for teaching speaking - Burhanuddin Yasin; Zulfadli A Aziz; Raudhatul Jannah (English Education Journal, 2017)
This research was done to investigate whether the lesson plans designed by the teacher matched the principles and methods of the CLT approach, how the teacher implemented the CLT approach for teaching speaking skills and what learning performances resulted from using CLT. The participants were senior high school students from classes X IPA, X MAK, XI IPA, XI MAK, and XII MAK plus the English teacher from Insan Qurani boarding school. The instruments used were observation sheets and documentation consisting of the teacher’s lesson plan and the students’ test results. The results from this study showed that there were several main procedures of the techniques suggested by the experts which were not completely written into the lesson plan. There were also several activities written into the lesson plans that were not performed well in the classroom. Furthermore, from the speaking performances produced by the students many of them did not reach the minimum passing criteria (KKM) of 70, although they had been treated with the CLT approach with role play, jigsaw, group discussions, picture series, and storytelling technique in their speaking classes. This leads to the conclusion that the students’ failure was because the procedures suggested by the experts were not entirely and effectively implemented by the teacher in her teaching.